2015
DOI: 10.1080/13504509.2015.1069766
|View full text |Cite
|
Sign up to set email alerts
|

Technological innovation for sustainable development: an analysis of different types of impacts for countries in the BRICS and G7 groups

Abstract: Technological innovation is considered as being one of the major driving forces in fostering economic growth. However, in the current economic situation, where matters related to environmental protection and conservation play a key role, technological innovation can also be used as a driver of new production alternatives to reduce the harmful impacts of industrial development on society and nature. Within this context, this paper aims to analyze, through econometric tools, the relationship between investments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…Similarly, Töbelmann and Wendler (2020) found an adverse impact of technological innovations on environmental degradation due to increases in the usage of renewable energy in the energymix structure and also improve environmental quality. Many studies have explored the relationship between technological innovations and environmental degradation across the globe and found a negative influence on environmental degradation (Chen and Lee 2020; Yu and Du 2019; Brandão Santana et al 2015;Zhou et al 2016;Gerlagh 2007;Sagar and Holdren 2002;Canadell et al 2007;Sohag et al 2015;Kverndokk et al 2004;Costantini et al 2017;Ang 2009;Fei et al 2014). Other studies explored that technological innovations may degrade the environmental quality due to a lack of research and development (R&D) investment so the desired level of TE has not been attained so for Cheng et al 2019, Gu and Wang (2018), Kivyiro and Arminen (2014), and Yongping 2011).…”
Section: Technological Innovations and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Töbelmann and Wendler (2020) found an adverse impact of technological innovations on environmental degradation due to increases in the usage of renewable energy in the energymix structure and also improve environmental quality. Many studies have explored the relationship between technological innovations and environmental degradation across the globe and found a negative influence on environmental degradation (Chen and Lee 2020; Yu and Du 2019; Brandão Santana et al 2015;Zhou et al 2016;Gerlagh 2007;Sagar and Holdren 2002;Canadell et al 2007;Sohag et al 2015;Kverndokk et al 2004;Costantini et al 2017;Ang 2009;Fei et al 2014). Other studies explored that technological innovations may degrade the environmental quality due to a lack of research and development (R&D) investment so the desired level of TE has not been attained so for Cheng et al 2019, Gu and Wang (2018), Kivyiro and Arminen (2014), and Yongping 2011).…”
Section: Technological Innovations and The Environmentmentioning
confidence: 99%
“…Technological innovation (TE) is one of the most authentic ways to reduce environmental degradation and also improve economic growth (Chen and Lee 2020;Yu and Du 2019;Brandão Santana et al 2015;Zhou et al 2016;Gerlagh 2007;Canadell et al 2007;Sohag et al 2015). The 12th BRICS summit was held on November 17, 2020, virtually meeting due to the coronavirus disease 2019 (COVID-19) pandemic and has done many agreements in the field of science, technology, and innovation sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Companies may depend on their competitiveness through technological capabilities to produce innovative results with reasonable confidence to provide competitive goods and services to customers while growing market share and to increase business income [51], and they are delivering a higher reward for workers. Therefore, companies can expand current methods and enhance resource utilization through technological capabilities while reducing resource consumption and relieve environmental pressure [52,53]. _ENREF_31Porter and Van der Linde [54] find that firms that incorporate CEP into technological capabilities would take measurements in the market, which is one of the reasons companies can achieve a competitive advantage.…”
Section: Corporate Environmental Performance (Cep) and Technological mentioning
confidence: 99%
“…Enterprises can rely on their own strength through technological innovation, in good faith, to obtain innovative results with which to provide consumers with satisfactory products and services while winning market share, increasing corporate income [20] and providing higher compensation for employees. In addition, enterprises can improve existing processes and improve resource utilization through technological innovation, thereby reducing wastage of resources and lightening the environmental burden [21,22]. Porter and Linde found that enterprises that integrate social responsibility into technological innovation will take the initiative in the market, which is one of the means for enterprises to acquire core competitiveness [23].…”
Section: The Relationship Between Csr and Technological Innovation Inmentioning
confidence: 99%